2021
DOI: 10.1111/ijac.13828
|View full text |Cite
|
Sign up to set email alerts
|

The effects of adding nano‐alumina filler on the properties of polymer‐derived SiC coating

Abstract: In this paper, SiC coating was prepared using the polymer‐derived ceramic method; then the effect of nano‐alumina as a filler material was studied. First of all, polycarbosilane(PCS) was dissolved in xylene; after that, different amounts of nano‐alumina particles were added to the solution. The coating was deposited on the alumina substrate using the dip‐coating method; this was followed by sintering at 1200℃. The phase content and microstructure of the samples were studied by X‐ray diffraction and scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…There are different kinds of amorphous Si such as amorphous silicon carbide (a-SiCss), amorphous silicon germanium (a-SiGe), microcrystalline silicon (m-Si), and amorphous silicon-nitride (a-SiN). Amorphous cells are prepared by a chemical vapor deposition process in which Silane gas (SiH 4 ) is heated up to 200-300 °C in radio frequency plasma [65,99]. Amorphous cells have a high energy bandgap (1.7 eV) and 40 times higher rate of light absorption due to their random structure as compared to mono-crystalline (1.1 eV) [100].…”
Section: Amorphous Silicon Solar Cellmentioning
confidence: 99%
“…There are different kinds of amorphous Si such as amorphous silicon carbide (a-SiCss), amorphous silicon germanium (a-SiGe), microcrystalline silicon (m-Si), and amorphous silicon-nitride (a-SiN). Amorphous cells are prepared by a chemical vapor deposition process in which Silane gas (SiH 4 ) is heated up to 200-300 °C in radio frequency plasma [65,99]. Amorphous cells have a high energy bandgap (1.7 eV) and 40 times higher rate of light absorption due to their random structure as compared to mono-crystalline (1.1 eV) [100].…”
Section: Amorphous Silicon Solar Cellmentioning
confidence: 99%
“…The electrical conductivity of PDCs from insulator to conductor varies widely depending on their microstructure and composition, which are finally determined by the molecular structure of the preceramic precursors, pyrolysis conditions (temperature, atmosphere, holding time), and processing techniques. The electrical properties of PDCs can be improved easily by adjusting their compositions (e.g., integrating PDCs with conductive frameworks, [82][83][84][85][86] heteroatom doping into PDCs, [87][88][89][90] addition of filler particles to the preceramic polymer matrix [91][92][93][94][95] ). Shao et al designed a graphene aerogel/SiOC heterostructure, for example, by infiltrating a preceramic polymer into a 3D-reduced graphene oxide aerogel followed by a pyrolysis process.…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…The electrical properties of PDCs can be improved easily by adjusting their compositions (e.g., integrating PDCs with conductive frameworks, 82–86 heteroatom doping into PDCs, 87–90 addition of filler particles to the preceramic polymer matrix 91–95 ). Shao et al.…”
Section: Polymer‐derived Ceramics (Pdcs)mentioning
confidence: 99%
“…In view of the merits of nano Al 2 O 3 , scientists have carried out extensive research. Yousefi et al [ 23 ] studied the effect of nano alumina filler on the mechanical properties of polymer-derived SiC coating firstly, found that 20% of nano alumina can activate the nucleation of SiC fiber and effectively improve the mechanical properties of the coating. Pitawala et al [ 20 ] explored the influence of nano porous Al 2 O 3 on the thermoelectric transport performance of polymer electrolyte.…”
Section: Introductionmentioning
confidence: 99%